2011
DOI: 10.1002/cne.22569
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine‐ and amphetamine‐regulated transcript peptide (CART) in the telencephalon of the catfish, Clarias gariepinus: Distribution and response to fasting, 2‐deoxy‐D‐glucose, glucose, insulin, and leptin treatments

Abstract: The cocaine- and amphetamine-regulated transcript peptide (CART)-containing system in the forebrain of Clarias gariepinus was studied with immunocytochemistry. While the immunoreactivity was prominently seen in the neurons of the entopeduncular nucleus (EN) located in the ventral telencephalon, CART-immunoreactive fibers were widely distributed in the dorsal and ventral telencephalon. In view of the established role of CART in energy metabolism, we investigated the response of the CART immunoreactive system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 90 publications
3
38
1
Order By: Relevance
“…In rainbow trout IP administration of insulin inhibited (Librán-Pérez et al, 2015a) or activated (Polakof et al, 2008a; Conde-Sieira et al, 2010b) food intake whereas ICV treatment with insulin inhibited food intake in rainbow trout (Soengas and Aldegunde, 2004) but not in catfish (Silverstein and Plisetskaya, 2000). The putative anorectic effects of insulin would be in agreement with the increased anorexigenic potential elicited by insulin treatment as demonstrated increased mRNA abundance of CART in rainbow trout (Librán-Pérez et al, 2015a) and catfish (Subhedar et al, 2011) as well as decreased NPY mRNA abundance in rainbow trout (Librán-Pérez et al, 2015a). As for insulin capacity to modulate the activity of nutrient sensing systems, its administration in rainbow trout inhibits glucosensing response in hypothalamus, hindbrain, BB, and intestine (Polakof et al, 2007a, 2008a, 2010b; Conde-Sieira et al, 2010b).…”
Section: Endocrine Modulation Of Nutrient Sensingmentioning
confidence: 56%
See 2 more Smart Citations
“…In rainbow trout IP administration of insulin inhibited (Librán-Pérez et al, 2015a) or activated (Polakof et al, 2008a; Conde-Sieira et al, 2010b) food intake whereas ICV treatment with insulin inhibited food intake in rainbow trout (Soengas and Aldegunde, 2004) but not in catfish (Silverstein and Plisetskaya, 2000). The putative anorectic effects of insulin would be in agreement with the increased anorexigenic potential elicited by insulin treatment as demonstrated increased mRNA abundance of CART in rainbow trout (Librán-Pérez et al, 2015a) and catfish (Subhedar et al, 2011) as well as decreased NPY mRNA abundance in rainbow trout (Librán-Pérez et al, 2015a). As for insulin capacity to modulate the activity of nutrient sensing systems, its administration in rainbow trout inhibits glucosensing response in hypothalamus, hindbrain, BB, and intestine (Polakof et al, 2007a, 2008a, 2010b; Conde-Sieira et al, 2010b).…”
Section: Endocrine Modulation Of Nutrient Sensingmentioning
confidence: 56%
“…POMC mRNA abundance increased in response to leptin treatment in rainbow trout (Murashita et al, 2008; Aguilar et al, 2011; Gong et al, 2016a). Leptin treatment also increased CART mRNA levels in hypothalamus of goldfish (Volkoff and Peter, 2001), catfish (Subhedar et al, 2011), and rainbow trout (Murashita et al, 2008; Aguilar et al, 2011; Gong et al, 2016a). Furthermore, leptin receptor knockout for medaka displayed (compared with the wild type) a higher food intake, as well as decreased POMC mRNA abundance, and increased NPY and AgRP mRNA abundance (Chisada et al, 2014) whereas zebrafish knockout for leptin displayed changes in mRNA abundance of genes related to glucose but not to lipid metabolism (Michel et al, 2016).…”
Section: Endocrine Modulation Of Nutrient Sensingmentioning
confidence: 98%
See 1 more Smart Citation
“…The specificity of this antibody has been demonstrated by omission of primary antibodies and by immunoblot analysis showed a single precipitin band that migrates at about 14 kD (Subhedar et al, 2011; Singru et al, 2007). Within the basal ganglia, CART is a marker for neurons in the medial part of the accumbens shell in diverse vertebrate species, (Smith et al, 1999; Lázár et al, 2004; Barsagade et al, 2011; Subhedar et al, 2011), which is consistent with the labeling pattern observed in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Fasting/food restriction decreases CART brain expression in Cypriniformes (goldfish Volkoff and Peter, 2001a, zebrafish Nishio et al, 2012; Guillot et al, 2016 and common carp, Wan et al, 2012), most Characiformes (red-bellied piranha Volkoff, 2014a, and pacu Volkoff et al, 2017), most Salmoniformes (Atlantic salmon, Murashita et al, 2009a; Kousoulaki et al, 2013, rainbow trout Figueiredo-Silva et al, 2012), Atlantic cod (Kehoe and Volkoff, 2007), cunner (Perciforme) (Babichuk and Volkoff, 2013), medaka (CART3) (Murashita and Kurokawa, 2011), and Siluriformes (channel catfish Kobayashi et al, 2008, African sharptooth catfish Clarias gariepinus Subhedar et al, 2011), suggesting an anorexigenic role for CART in teleost fish. Postprandial increases in CART brain expression have been shown in Senegalese sole (CART1a, CART 2a and CART4) (Bonacic et al, 2015), pacu (Volkoff et al, 2017), dourado (Volkoff et al, 2016), channel catfish (Peterson et al, 2012) but not in cod (Kehoe and Volkoff, 2007).…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%